2022
DOI: 10.3390/agriculture12060873
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Bacterium from Non-Agricultural Soil Improves Okra Plant Growth

Abstract: Beneficial soil microorganisms influence nutrient recycling, soil fertility, plant growth, and productivity and reduce chemical fertilizer application. This study aimed to isolate bacteria from non-agricultural soils in the Al-Ahsa region and characterize the bacteria with the best biostimulating characteristics at the physiological, biochemical, and molecular level. DPM17, a bacterial isolate, promotes plant growth through phosphate solubilization, nitrogen fixation, and ammonia production. DPM17 also produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The four selected strains were identified as Rhizobium, Ensifer, and Pseudomonas (Table 2), indicating that their growth-promoting ability is not exclusive to a particular genus. The isolated strains used in our study showed some plant growth-promoting properties, and the same PGPR properties in okra plant growth have been previously reported [44,45,74,75]. Hence, multiple pathways exist to increase the growth of okra, and endophytic bacteria have different combinatorial growth-promoting properties.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The four selected strains were identified as Rhizobium, Ensifer, and Pseudomonas (Table 2), indicating that their growth-promoting ability is not exclusive to a particular genus. The isolated strains used in our study showed some plant growth-promoting properties, and the same PGPR properties in okra plant growth have been previously reported [44,45,74,75]. Hence, multiple pathways exist to increase the growth of okra, and endophytic bacteria have different combinatorial growth-promoting properties.…”
Section: Discussionsupporting
confidence: 77%
“…Three inoculated strains, which did not have IAA-producing activity (Table 2), also showed okra growth-promoting ability (Figure 2), indicating that there are other ways to induce okra growth. In addition to the IAA production, other mechanisms of plant growth promotion have been reported as follows: ACC deaminase production [75,81], phosphate-solubilizing abilities [44,74,82], cellulase-pectinase activity [26,83], siderophores production [44,84], nitrogen fixation [81], organic acid production, and production of plant hormones such as IAA [44,74,75], gibberellic acid (GA3) [85], and cytokinins [74,86]. In the present study, each of the four isolates exhibited ACC deaminase activity, with Okhm3, Okhm10, and Okhm11 demonstrating phosphorus solubility (Table 2), suggesting that there are multiple pathways to promote okra plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…IAA increases ACC production via ACC synthetase [ 24 ], and AZC66 increases plant growth via IAA production. AZC66’s growth on nitrogen-free Jensen’s medium may suggest nitrogen fixation [ 25 , 26 ]. Nitrogenase, a complex enzyme, fixes nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…and Enterobacter spp. Bacillus, Pseudomonas and Enterobacter were the most common genera of endophytic bacteria isolated from different healthy plant species ( AlAli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%